Radio-frequency wall conditioning for steady-state stellarators - Kulyk, Yu.S.; Moiseenko, V.Е.; Wauters, T.; Lyssoivan, A. (Вопросы атомной науки и техники, 2016)
Results of numerical modelling of a pulsed discharge used for wall conditioning and sustained by excitation of slow waves at frequencies below the ion cyclotron are presented. The analysis carried out with usage of a selfconsistent model that simulates plasma production. The numerical calculations have shown that at the plasma buildup stage, the atoms are generated mainly owing to dissociation of hydrogen molecules by electron impact. When the RF power is off the dissociative recombination of molecular ions with electrons comes to play that is an additional source of atomic hydrogen.